Avaliação de diferentes campos de força para descrição do equilíbrio líquido vapor de misturas contendo sulfeto de hidrogênio - Pirete, Marcelo Melo (2019)
It is usual to find hydrogen sulfide (H2S) in oil and natural gas production, it´s estimated that around 30% of the world's natural gas production contains this contaminant (SKRITC, 2006). Therefore, it is required the design of H2S removal units for transport and sales specification. However, under the pressure conditions of the productive units, there is a lack of experimental data leading to difficulty in validating thermodynamic models capable of describing this system. The use of molecular simulation has allowed the evaluation of several phenomena under conditions where experiments are difficult. Thus, the present work presents an evaluation on the influence of the force fields on the prediction of the liquid vapor equilibrium (ELV) of the binary mixtures H2S with CO2 and CH4. The work uses the popular force field models presented in the literature to represent hydrogen sulfide in combination with methane and carbon dioxide represented by grouped atom model - United Atom (UA) and explicit Atom (AA) models. The results were compared with experimental and simulation data previously reported in the literature. It was observed that the use of simplified United Atom molecular models to represent CH4 and CO2 presented satisfactory performance, with the possibility of improvement with the use of new combining rules. It was observed also a good performance with the application of the model proposed by Zhang e Duan (2015) for CO2 in binary and ternary mixtures with H2S.